Implementasi Kepatuhan Wajib Pajak melalui Pelaporan SPT Tahunan Orang Pribadi - Syarifuddin, Safria; Ilham, Ilham; Arifin, Rukminih; Sari, Sri Nirmala; Denka, Veronika Sari; Gisda, Ardyansyah (Pakis Journal Institute, 2025)
This tax volunteer internship activity aims to provide real contributions to the assistance and reporting services for Individual Annual Tax Returns at the South Sulawesi Regional Kanwil DJP. With assistance and training for taxpayers related to accessing the official website of the Directorate General of Taxes (DJP), djp.online.pajak.go.id, and filling out the SPT OP. I trust that taxpayers at the South Sulawesi Kanwil DJP can enhance their awareness of income tax reporting, thereby expanding state revenue and promoting economic growth in Indonesia. Additionally, through this assistance, I aim to share knowledge with taxpayers, enabling them to report their income tax autonomously. With the presence of charge volunteers who contribute, it is expected that taxpayers at the Kanwil DJP of South Sulawesi can effectively recognize and comply with tax controls applied in Indonesia, so that it can have a positive impact on the assess economy and citizen welfare. This study gives a comprehensive insight into the collaboration between charge volunteers and officials from the teaching, and can at that point optimize the viability of assistance and socialization activities, as well as tax education. Taxpayer compliance and e-filing mechanisms are still obstacles to submitting annual tax returns. One of the strategies for Tax Mindfulness Inclusion in Education is the charge volunteer program. Bosowa Polytechnic is actively involved in implementing this tax volunteer program through a community service program. Annual Tax Returns and Periodic Tax Returns for PPh OP.